PENGARUH α-CASE DAN ANGKA KEKERASAN (SIFAT MEKANIK) TERHADAP LAJU PERUBAHAN ELONGASI (DEFORMASI) MATERIAL Ti6AL4V HASIL PROSES SUPERPLASTIS FORMING - Armila Armila (Jurnal Teknik Mesin (JTM), 2012)
Superplastic materials may be stretched in tension to elongations typically in excess of 200% and more commonly in the range of 400–2000%. There are rare reports of higher tensile elongations reaching as much as 8000%. The high ductility is obtained only for superplastic materials and requires both the temperature and rate of deformation (strain rate) to be within a limited range. The temperature and strain rate required depend on the specific material. A variety of forming processes can be used to shape these materials; most of the processes involve the use of gas pressure to induce the deformation under isothermal conditions at the suitable elevated temperature. The tools and dies used, as well as the superplastic material, are usually heated to the forming temperature. There are a number of commercial applications of super-plastic forming for aerospace, Examples are wing access panels in the Airbus A310 and A320, bathroom sinks in the Boeing 737, turbo-fan-engine cooling-duct components, external window frames in the space shuttle, front covers of slot machines.